Demografía de Especies Maderables de la Península de Osa - Quesada-Monge, Ruperto; Castillo-Ugalde, Marvin; Lobo-Segura, Jorge; Barrantes, Gilberto (Instituto Tecnológico de Costa Rica, 2010)
This project is supported by 20 years of research and previous projects that have been carried out in the Osa Peninsula by researchers at the TEC Forestry School, all with the common interest of generating baseline information for the management of the forests in the Osa Peninsula. The main objective was to “determine the population demographics of the most intensively harvested merchantable tree species in the Osa Peninsula”. Three research sites within the Golfo Dulce Forest Reserve were selected. Within each site four 1-ha permanent plots were established during the “Forest Management Alternatives” project conducted in 1990 and 1993 (Castillo, 1990, Cordero, 1990). Demographic parameters are presented for five merchantable species in the Osa Peninsula (Peltogyne purpuea, Caryocar costaricense, Copaifera camibar, Qualea polychroma y Aspidosperma spruceanum). Growth rate, mortality and recruitment for early and late successional species were determined using data collected in three censuses within the permanent plots. Additionally, demographic matrices were built to predict the size of the populations in 45 years and the effect of selectively logging 50% of all trees was determined for a 15-year cutting cycle which is the norm for management plans usually approved by the Osa Conservation Area. Predictions of tree demographics after harvestings in which 50% of all trees are selectively logged every 15 years show a rapid decrease in the late successional species in the short term (<30 years), and would also cause depletion of important merchantable species in all successional stages due to the low recruitment of advanced regeneration. Particularly, this negatively affects P. purpurea, C. costaricense y C. Camibar and results show that this management regime could cause the local extinction of these species. On the contrary, A. spruceanum and Q. poylchroma were observed to recover more quickly after harvestings and this is due to their higher growth rates and their population structure. Overall, it is recommended that the current Forestry Law should be modified to decrease the extraction rate of these tree species. Thus, cutting cycles should be extended and harvesting intensities should be modified in order to increase the time period in between harvestings. This analysis was based on several silvicultural treatments implemented in the simulations, which are based on three different silvicultural systems (Cordero and Howard, 1990; Castillo, 1991). 1. Improved traditional system: it is the traditional harvesting method of felling and skidding. The planning of forestry operations can thus reduce damage to the forest. Because of this, directional felling should be practiced to reduce the amount of damage to standing trees, the forest floor and extracted logs. During the skidding process, the machinery should remain in the skid trails and all logs must be extracted by using cables (i.e. winched) in order to reduce road distance and the damaged cause by machinery in the forest. 2. Skidding with oxen: the oxen are equipped with chains and a skidding wooden frame. The damaged cause by machinery in the forest is thus reduced. 3. Traditional skidding system with tractors: most common method employed in the country which is highly damaging to the forest, and without prior planning can cause great deterioration of the ecosystem. From the above described skidding methods the different silvicultural systems are derived: Oxen skidding method (SACB), Improved traditional system (SATM), Traditional skidding system with tractors (SATT) and Improved skidding method with oxen and tractors. Regarding tree density (N/ha), there is a tendency to increase with time, which suggests a recovery of the forest after harvestings. In primary forests tree density was 435,6 trees/ha. Tree density also varied from 350 trees/ha in the SATT treatment to 435 trees/ha in the SACB treatment, with a difference between treatments of 85 trees/ha. Nonetheless, 15 years after the first harvesting tree density changed to 520 trees/ha in the SACB and 569 trees/ha in the SABT treatment, reducing the difference between treatments by 50%. There is an increase in the basal area (m2 /ha) 15 years after the harvesting, although values similar to those in primary forests have not been reached yet. In primary forests the average basal area was 30,12 m2 /ha and, specifically for 2007 it was 29,43 m2 /ha. Basal area (m2 /ha) was high regardless of its decrease due to the silvicultural treatments, and when compared with other humid forests this site ranks high. For example, in Northern Costa Rica primary forests have been reported to present 23,8 m2 /ha, and in logged forests it may ranged from 17 to 21,2 m2 /ha. In the development curve analysis, it is important to notice the problem with the abundance of individuals according to their DBH distribution. Not all species reach the canopy or are very abundant so the strategies for their survival/permanence change. In this way, the development curves vary dramatically and are related to the autoecology of the species, which are in turn affected by forest management practices. Tree growth is influenced by many factors, nonetheless, when forests are being assessed for forest management the degree of disturbance caused by the harvestings becomes an important factor since it modifies the standing vegetation and this is tailored according to the particular growth rates of the species. In these experiments, current annual growth (ICA) was 2,88- 3,21 cm/year and the highest current annual growth value of 3,1 cm/year was reported for the most severe treatment. For a 12-year period, and related to the silvicultural treatments implemented, certain tendencies in species’ behaviors have been observed: current annual growth tends to be greater in the 30-39,9 cm at DBH and the 50-59,9 cm at DBH categories, but then decreases considerably in larger categories; this trend is clear in all four treatments. The species with the highest diameter increment by treatment are: Vochysia ferruginea with 15,58 mm/year in treatment 1, Vochysia allenii with 18,17 mm/year, and 12,72 mm/year in treatments 2 and 4, respectively, and Tachigali versicolor with 13,3 mm/year in treatment 2. The proceeding demonstrates these species’ potential for growth. Growth rates are high, Vocyhsia alleni was shown to have the highest growth rate at 12,53 mm/year. This highlights the 12-year growth interval considered in this analysis, which is highly significant. Other equally important within this forest are: Brosium utile, Qualea polychroma, Simarouba amara, Symphonia globurifera, Tapirira myriantha and Vochysia megalophylla were present in all four treatments and present high current annual growth rates. At the other extreme, 67 species are only found in one of the treatments and demonstrate current annual growth rates of 5mm per year. This demonstrates the high variability in terms of growth rates that exists within tropical forests. Growth curves of species with high importance or economic values are presented. These species are Qualea polychroma, Peltogyne purpurea, Calophyllum brasiliense, Carapa nicaraguensis, Brosimun utile, Symphonia globulifera. Species in different genera but with similar ecological charactgeristics were grouped: Vochysia (V. allenii, V, ferruginea, V. guatemalensis, V. megalophyla), Virola (V. koschny, V. sebifera), and at the family level: Sapotaceae (géneros Pouteria, Elaeoluma, Micropholis, Manilkara), and lastly the shade-intolerant and fast-growing species: Trattinnicka aspera, Laetia procera, Apeiba membranaceae, Cecropia obtusifolia, C. insignis, Jacaratia spinosa, Casearia arborea, Jacaranda caucana, and Castilla tunu. All of these present the typical hyperbole curve in their distributions. With respect to mortality among treatments, results indicate that treatment III SATT presented the highest mortality rates, and treatment IV SABT presented the highest recruitment rates. The current tendency is where disturbances were greater mortality was high. Ecological guilds are used in grouping species presenting similar autoecological characteristics in relation to their shade-tolerance. From a silvicultural perspective, this classification allows to assess forest growth after the treatments by means of DBH growth. From the disturbance viewpoint, treatment 4 was the most severe, and it is to be expected that shade-intolerant species present the highest current annual growth rates. This was confirmed and for the fast-growing shade-intolerant species and the pioneer species which attained 4,22 – 4,29 mm/year of DBH growth per year, respectively. It was also observed that the shade-intolerant group presents the highest current annual growth in all treatments, which was also to be expected. An important objective in this project was to translate demographic information into practical recommendations for extraction rates and harvesting methods for the study species. Being able to monitor species for 17 years provides very valuable information that sheds light on the ecology of the tree species, on their growth rates, and silviculturally by studying their response to different silvicultural regimes. This information together is useful when designing sustainable forestry practices for the forests in the Osa Peninsula. After the publication of the Standards for Sustainable Natural Forest Management, according to the Executive Decree 34559-MINAE, published in the Gaceta 115 on June 16th, 2008, the use of the Practices Code and the Manual of Procedures is enforced thereon. This decree demands the application of reference values for two very important variables: basal area (m2 /ha) and the ranges of absence/presence of species according to their ecological guild. Because this decree enforces its implementation in the country, data from two very specific sites was used to establish these guidelines: Northern Costa Rica and the area of influence of FUNDECOR (Foundation for the Development of the Central Cordillera), and there are differences in the variables discussed here between sites. To have more specific parameters of forest dynamics in this region, the Osa Conservation Area (ACOSA) has planned to generate new reference values for this region, and for this reason this study’s results become very valuable, because it provides up to date information which has been requested to the researchers working in the area by ACOSA. Given the importance of this request, the dissemination of the findings in this study can be readily distributed and incorporated into the different government sectors. Meetings were carried out between the ACOSA officials and the researchers, with the objective of designing a strategy that could be submitted to the National Commission of Sustainable Forestry in order to modify the current Executive Decree 34559-MINAE. This project’s results suggest that the reference values set by the Executive Decree 34559-MINAE are small compared to the values reported in the Osa Peninsula’s forests. This represents a disadvantage for these forests because they are harvestable according to the decree. This is mainly due to the fact that the Peninsula’s forests are more productive than most forests in the country.
Proyecto de investigación (Código 5402-1401-8401) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería Forestal. Centro de Investigación en Integración Bosque; Universidad de Costa Rica. Escuela de Biología, 2010
Keywords: Bosques; Parámetros; Fustales; Crecimiento; Probabilidades